2020
DOI: 10.3390/rs12101578
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Citizen Science Smartphone Apps for Inland Water Quality Assessment

Abstract: Rapid and widespread monitoring of inland and coastal water quality occurs through the use of remote sensing and near-surface water quality sensors. A new addition is the development of smartphone applications (Apps) to measure and record surface reflectance, water color and water quality parameters. In this paper, we present a field study of the HydroColor (HC, measures RGB reflectance and suspended particulate matter (SPM)) and EyeOnWater (EoW, determines the Forel–Ule scale—an indication to the visual appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 52 publications
3
30
0
Order By: Relevance
“…HydroColor can be downloaded from App stores and has been applied and validated by several studies. Malthus et al [ 21 ] used HydroColor to collect water images from 32 sampling stations in eastern Australia to calculate water leaving reflectance, which was compared with in situ measurements. The accuracy of HydroColor was lower when the surrounding water environment was complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HydroColor can be downloaded from App stores and has been applied and validated by several studies. Malthus et al [ 21 ] used HydroColor to collect water images from 32 sampling stations in eastern Australia to calculate water leaving reflectance, which was compared with in situ measurements. The accuracy of HydroColor was lower when the surrounding water environment was complex.…”
Section: Introductionmentioning
confidence: 99%
“…This assumes that there is a linear relationship between camera-measured digital pixel number (DN) values and the incident light radiance, which is the basis of the water leaving reflectance derivation and water quality parameter inversion. However, studies have shown that the linear relationship hypothesis between the DN and incident light radiance in HydroColor is not accurate [ 21 , 23 , 24 ]. Therefore, the purpose of this study was to develop a method to simulate the nonlinear relationship between the DN and incident light radiance by multiple reflectance reference cards, thereby deriving water leaving reflectance from the nonlinear corrected DN in digital images.…”
Section: Introductionmentioning
confidence: 99%
“…Water color, as perceived by the human eye, is an integrative measure of water quality. It can be scaled to rivers globally and measured across multiple sensor platforms from human eyes (Garaba et al., 2015) to cell phone cameras (Leeuw & Boss, 2018; Malthus et al., 2020) to satellites. The intuitive and easily observable nature of water color could enable collection of massive volumes of data across spatial and temporal scales for water quality monitoring, identifying global hotspots of change, and advancing macrosystems ecology in rivers.…”
Section: Resultsmentioning
confidence: 99%
“…Significant filtration was needed to obtain data points which really fulfilled the scientific criteria for a research study (Figure 9B). In a similar citizen science project using FU index to measure water colour of Australian inland waters, Malthus et al (2020) have reported difference of more than 2 FUI units between the observer data and the photo-based colour code in only 3% of the cases. Therefore, the reason for the larger bias in our case needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%